Determining The Success of The Mary The Queen College’s (MQC) Accountancy Graduates In The CPA Board Exams Using Program Theory Framework - Lapid, Michael B. (International Business Education Journal, 2015)
The paper aims to evaluate the effectiveness of the CPA Board Examination Review being administered by the Institute of Accountancy at Mary the Queen College of Pampanga, Inc. (MQCPI). The review program is part of the interventions being undertaken by the Institute to improve the performance of its graduates in the CPA licensure examination. In the assessment of the program, correlation analysis was utilized using linear regression. Several variables in connection with the review program were correlated with the actual CPA board examination ratings of the graduates of the Institute. The results suggest that the Institute should focus its resources on improving and/or strengthening the following areas: faculty selection process, physical facilities, basic courses in the BS in Accountancy program, library holdings and review materials. Amidst the stiff competition in private higher education nowadays, academic institutions such as MQCPI must see to it that interventions undertaken to improve curricular programs must be cost effective. As such, the Program Theory framework becomes an effective tool in this endeavor.